Spatial heterogeneity of arsenic in a deltaic groundwater environment of West Bengal, India - Chatterjee, D.; Majumder, S.; Biswas, A.; Sarkar, S.; Kundu, A.; Mukherjee, Abhijit; Bhowmick, S.; Roman-Ross, G.; Chatterjee, D.; Neidhardt, H.; Berner, Z. (2012)
The water quality and chemistry of the groundwater samples collected from rural West Bengal have been investigated. The investigation focuses on the multiple As mobilization processes taking place simultaneously. The groundwater arsenic (As) distribution and their relationships with land-use pattern suggest the influence of local conditions (e.g. sanitation, presence of surface water bodies, agricultural practice). The As release mechanism is complex with observation of patchy (spatio-vertical heterogeneity) As hot spots. Unique/individual mechanism is difficult to link with the heterogeneous distribution of As. Local conditions may contribute to some extent to explain the heterogeneity in arsenic distribution and mobilization pattern along with geology and hydrogeology. © 2012 Taylor & Francis Group.